Frankies For You (FFY) - Dave, Shruti; PatDela, Rajendra; Premchander (London : SAGE Publications Ltd, 2017)
Frankies For You is a comprehensive case on standard costing. It stresses the importance of adopting cost control tools like budgeting by small organizations. FFY is a small food joint started by Mr. Raj Singh. After the first month of operation, he finds that though sales volume has increased compared to the budget, the actual profit has fallen. Detailed variance analysis has to be used to find the cause for this anomaly, to evaluate the performance of the staff and to assign responsibilities. The case also refers to Activity Based Pricing, an important contemporary costing principle.
Originally published: Dave, S., & Patel, R. (2013). Frankies for you (FFY). F&A0503. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Singh, Raj; Frankies For You; Fast food restaurants -- Case studies; Food service management -- Case studies; Food service -- Cost control -- Case studies; Food industry and trade -- Case studies